2009
DOI: 10.1080/17470210902883263
|View full text |Cite
|
Sign up to set email alerts
|

Short article: When are moving images remembered better? Study–test congruence and the dynamic superiority effect

Abstract: It has previously been shown that moving images are remembered better than static ones. In two experiments, we investigated the basis for this dynamic superiority effect. Participants studied scenes presented as a single static image, a sequence of still images, or a moving video clip, and 3 days later completed a recognition test in which familiar and novel scenes were presented in all three formats. We found a marked congruency effect: For a given study format, accuracy was highest when test items were shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 20 publications
(33 reference statements)
2
33
0
Order By: Relevance
“…Scenes which were moving in the study phase were remembered better than scenes which were static, and performance was improved when the mode of presentation at test was the same as at study. These results were not dependent on the presence of a face in the scene; the dynamic superiority and study-test congruency effects reported by Matthews et al (2007) and Buratto et al (2009) are general phenomena which are not restricted to scenes containing moving faces. (Note that this experiment was not concerned with comparing the absolute memory for "hands" and "face" stimuli, only with showing that the same patterns of results hold for both types.)…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Scenes which were moving in the study phase were remembered better than scenes which were static, and performance was improved when the mode of presentation at test was the same as at study. These results were not dependent on the presence of a face in the scene; the dynamic superiority and study-test congruency effects reported by Matthews et al (2007) and Buratto et al (2009) are general phenomena which are not restricted to scenes containing moving faces. (Note that this experiment was not concerned with comparing the absolute memory for "hands" and "face" stimuli, only with showing that the same patterns of results hold for both types.)…”
Section: Discussionmentioning
confidence: 70%
“…Dividing attention may render observers less able to encode the perceptual details of the studied scenes, including their movement status, reducing the study-test congruency effect reported by Buratto et al (2009). On the other hand, if the encoding of movement status is automatic and relatively effortless, dividing attention will not modulate the effect.…”
Section: Memory For Moving Scenesmentioning
confidence: 96%
See 3 more Smart Citations